Painting masterclass : creative techniques of 100 great artists - Hodge, Susie, 1960- (London : Thames & Hudson, 2019)
Painting Masterclass explores the act of vision of the world's great artists, describing how their work was created to allow you to weave some of their magic into your own paintings. With detailed analyses and instructive creative tips sections, you can learn how to convey movement like Degas, apply acrylic like Twombly, and command colour like Matisse. The book is organized into seven chapters covering important genres: nudes, figures, landscapes, still life, heads, fantasy and abstraction. Each chapter selects a cross section of artists and examines their practice in detail, using key paintings. Each artist is described through one of 100 selected masterpieces, plus a biographical profile and a practical look at the way the painting was made: the materials and technique, an examination of the ideas and inspiration behind its making and how the artist's life might reflect their concerns. Light and shade, rhythm, form, space, contour and composition are all covered in detail. The book covers a broad historical and geographic sweep, and includes many of the most celebrated male and female artists.
-- Introduction -- Creative tips and techniques -- Basic materials -- Accessories -- Basic painting techniques -- Nudes -- Figures -- Landscape -- Still life -- Heads -- Fantasy -- Abstractions -- Glossary -- Index.
Includes index.
Keywords: Painting -- Technique; Painters